Pre-hospital and hospital traumatic deaths in the former homeland of Transkei, South Africa - Meel, B.L. (Journal of clinical forensic medicine, 2004)
This retrospective descriptive study on 274 medicolegal cases was to determine the issues related to pre-hospital and hospital deaths in injured patients and to determine whether any of the deaths were preventable in the area. Interviews of the family members were conducted individually before carrying out autopsies. Time of survival after trauma, place of death, and the cause of death were recorded along with the demographic information – age, sex, occupation, and personal habits. Umtata General Hospital in the Eastern Cape Province is the referral hospital for a surrounding population of about 400,000. Seventy four percent (74%) of the victims had been declared, ‘presumably dead’ at the scene by the community or police, and taken to mortuary without any death certification by a physician. The rest (26%) were taken to hospital where later they succumbed to trauma. Out of these only 4% underwent surgery. The majority (68%) of the victims were young (<40 years). The causes of deaths were: motor vehicle accidents (MVA) 32%, gunshot 24%, stab injury 17%, blunt trauma 9% and miscellaneous (fall from height, burns, etc.) 17%. Head and chest injuries were the commonest 50%. Only 17% survived from days to weeks. About 75% subjects died within 6 h of the trauma. There is a very high pre-hospital (74%) mortality of trauma patients in the Transkei region. The fact that members of the community or police and not a medical practitioner confirmed deaths raises the ethical issue of right to life. Some may actually be alive when they are considered dead. As it appears that 12% of pre-hospital deaths are preventable, employing more medical personnel in the rural areas along with an effective ambulance service would seem to be required.